2007
DOI: 10.1017/s0033291707001420
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-month mental disorders in South Africa: prevalence, service use and demographic correlates in the population-based South African Stress and Health Study

Abstract: Background-South Africa's history and current social conditions suggest that mental disorders are likely to be a major contributor to disease burden, but there has been no national study using standardized assessment tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
191
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(209 citation statements)
references
References 18 publications
16
191
1
1
Order By: Relevance
“…In the general population, the 12-month prevalence of any Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV)/Composite International Diagnostic Interview (CIDI) mental disorder in a national epidemiological study was 16.5%, with 26.2% of respondents classified as severe cases and an additional 31.1% as moderately severe cases, indicating that mental health problems affect a large portion of the population. [4] The most pervasive mental health consequences of IPV and HIV in the SA context tend to be depression, post-traumatic stress disorder (PTSD) and alcohol/substance use disorders. [4][5][6] It is also likely that all three disorders are comorbid in this population, requiring a nuanced treatment plan that integrates management of all through one feasible intervention.…”
Section: Intersecting Epidemicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the general population, the 12-month prevalence of any Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV)/Composite International Diagnostic Interview (CIDI) mental disorder in a national epidemiological study was 16.5%, with 26.2% of respondents classified as severe cases and an additional 31.1% as moderately severe cases, indicating that mental health problems affect a large portion of the population. [4] The most pervasive mental health consequences of IPV and HIV in the SA context tend to be depression, post-traumatic stress disorder (PTSD) and alcohol/substance use disorders. [4][5][6] It is also likely that all three disorders are comorbid in this population, requiring a nuanced treatment plan that integrates management of all through one feasible intervention.…”
Section: Intersecting Epidemicsmentioning
confidence: 99%
“…[4] The most pervasive mental health consequences of IPV and HIV in the SA context tend to be depression, post-traumatic stress disorder (PTSD) and alcohol/substance use disorders. [4][5][6] It is also likely that all three disorders are comorbid in this population, requiring a nuanced treatment plan that integrates management of all through one feasible intervention.…”
Section: Intersecting Epidemicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cho et al (2009) found that in Korea only 6.1% of Korean adults who reported they had one or more psychiatric disorders accessed some form of professional mental health care within a year of being diagnosed. This percentage was found to be relatively lower when compared to other ethnic groups such as South Africans who reported 32.9% (Williams et al, 2008), 35% of Australians (Andrews, Henderson, & Hall, 2001) and 34.1% of Latinos and Asian Americans (Abe- . Korean people's low utilisation rates of mental health care could be explained by cultural factors such as stigma and culturally constructed knowledge of mental illness.…”
Section: Korean Migrants' Mental Healthmentioning
confidence: 79%
“…[1] It has also focused on assessing the role of traditional healers and traditional healing in relation to more conventional care. [2] Issues of mental health literacy [3] and explanatory models of mental illness [4] have been addressed.…”
mentioning
confidence: 99%